PEMBUATAN KUE KEMBANG GOYANG SUBSTITUSI TEPUNG IPOMOEA BATATAS LINNAEUS TERHADAP KUALITAS INDERAWI, KESUKAAN MASYARAKAT, MAUPUN KANDUNGAN PROTEIN DAN KADAR AIR: PEMBUATAN KUE KEMBANG GOYANG SUBSTITUSI TEPUNG IPOMOEA BATATAS LINNAEUS TERHADAP KUALITAS INDERAWI, KESUKAAN MASYARAKAT, MAUPUN KANDUNGAN PROTEIN DAN KADAR AIR - Safitri, Dini; Saptariana, Saptariana; Muhammad, Ansori; Fathonah, Siti (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2024)
Research on kembang goyang cake with substitution of Ipomoea batatas linnaeus (white sweet potato) flour to find out: 1) differences in sensory quality; 2) people's preferences for aspects of color, sweet taste, savory taste, aroma, and texture; 3) protein content and water content. This research consists of stages of sensory quality testing and people's liking tests.  20 somewhat trained panelists carried out the sensory test to assess the quality of the Kembang Goyang cake product, then analyzed using the average and continued with the ANOVA and Tukey tests. Test people's preferences using average analysis. The research results show: 1) there are differences in sensory quality in the aspects of color, sweetness, savory taste, aroma, and texture; 2) the highest average liking in the 0% sample was 4.06 (like), 10% was 4.06 (like), 20% was 4.21 (like), and 30% was 4.18 (like); 3) protein content of 8.12- 27.71% and water content of 0.78- 1.90. This indicates that there are differences in the sensory qualities and people's preferences for the Ipomoea Batatas Linnaeus flour kembang goyang cake. Keywords: Kembang Goyang Cake, People's Favorite, Sensory Quality, Ipomoea Batatas Linnaeus Flour